Oral health-related quality of life among people living with HIV and HIV-negative adults in Kigali, Rwanda: a comparative cross-sectional study - Julienne Murererehe; Yolanda Malele-Kolisa; François Niragire; Veerasamy Yengopal (BMC, 2024)
Abstract Background Assessing health-related quality of life has become integral to people living with HIV (PLHIV) follow-up. However, there is a lack of data regarding the impact of oral health on quality of life, known as Oral health-related quality of life (OHRQoL) among PLHIV compared to HIV-negative individuals in Rwanda. Aim The study aimed to assess OHRQoL among PLHIV compared to HIV-negative counterparts in Kigali, Rwanda. Methods The Oral Health Impact Profile short version (OHIP-14) questionnaire was interviewer-administered to 200 PLHIV and 200 HIV-negative adults (≥ 18 years old) at an HIV clinic of Kigali Teaching Hospital (CHUK). Socio-demographic characteristics, including age, sex, occupation, and socioeconomic status (SES) of participants, were collected using a survey questionnaire. A 4-point Likert scale was used to assess the frequency of oral impacts for all 14 items within 7 domains of the OHIP tool. The descriptive statistics were used to see frequencies and percentages of OHRQoL among PLHIV and HIV-negative persons, respectively. The Chi-square test was used to determine the association of OHRQoL with caries (DMFT) and periodontal disease (CPITN) among PLHIV compared to HIV-negative individuals. Results The results revealed a higher prevalence of PLHIV with poor OHRQoL than HIV-negative individuals in 5 domains and almost all items of OHIP-14 except for the OHIP 3 (found it uncomfortable to eat any foods because of problems with teeth or mouth) and OHIP-14 (being totally unable to function because of problems with teeth or mouth). The findings showed statistically significant results (p ≤ 0.05) for the OHIP1 item "trouble pronouncing any word," with a prevalence of 2.5% (n = 11) and 2.25% (n = 9) in PLHIV and HIV-negative, respectively. Also, PLHIV had a significantly higher prevalence, 2.75% (n = 11) for the OHIP 13 item "life not satisfying due to teeth and mouth problems compared to HIV-negative individuals 2% (8) p ≤ 0.05. Moreover, dental caries was significantly associated with poor OHRQoL among PLHIV and HIV-negative adults and for all 14 items of the OHIP tool. Periodontal disease was not significantly associated with OHRQoL among PLHIV and HIV-negative adults. Conclusion This study revealed poor OHRQoL among PLHIV compared to HIV-negative adults. There is a need for further longitudinal studies to investigate the OHRQoL in Rwanda, especially among PLHIV. It is essential to include oral health care as one of the components of the medical health care programs for PLHIV in Rwanda.